Philanthropy: Trends and Approaches A Case Study of Karachi - Jabeen, Huma; Khan, Fouzia Naeem (JISR management and social sciences & economics, 2008)
Societies comprise of different economic elements. According to the rule of nature, every individual is endowed with qualities and privileges, which set him/her apart from the other person. In order to overcome the inequalities, a society trains individuals to think as a collective whole. Understandably, if one behaves selfishly, then cooperation between individuals becomes impossible. Hence, certain practices of general benevolence exist in almost every society which is intended to provide a helping hand to the less fortunate. This is referred to as Philanthropy - the original Greek meaning of “love of mankind”. This word is often used as the embracive term for voluntary action for the public good. Philanthropy becomes an essentially contested concept when it is seen as a struggle between mercy and justice, between relief and development, between the alleviation of suffering and the reform of social institutions. Through the conducted study, we have tried to identify and examine the trends and approaches that exist in our society and the perception of a common man related to this noble act, which is an integral part of our religion and culture.